1993
DOI: 10.1172/jci116244
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation to increased dietary salt intake in the rat. Role of endogenous nitric oxide.

Abstract: Previous studies have suggested that nitric oxide (NO) plays a role in regulation of renal vascular tone and sodium handling.We questioned whether the effects of NO synthase inhibition on renal function are direct or due to increased renal perfusion pressure (RPP) and whether stimulation of endogenous NO activity plays a role in adaptation to increased dietary salt intake. Intrarenal arterial infusion of the NO synthase inhibitor NG-monomethyl-L-arginine (L-NMMA) in control rats resulted in decreased glomerula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

13
150
4
2

Year Published

1994
1994
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 242 publications
(169 citation statements)
references
References 44 publications
(59 reference statements)
13
150
4
2
Order By: Relevance
“…17 In rats, both acute and chronic administration of an NOS inhibitor causes renal vasoconstriction and a decrease in GFR as reported previously. 9,11,18,19 The present investigation also confirms that chronic L-NAME treatment induces decreases in total and regional blood flow to the kidney, as well as GFR, as compared with the values obtained from nontreated control animals. As observed with chronic tempol treatment in our earlier study, 6 acute intrarenal infusion of tempol in L-NAME-hypertensive rats in the present study also increased GFR.…”
Section: Discussionsupporting
confidence: 86%
“…17 In rats, both acute and chronic administration of an NOS inhibitor causes renal vasoconstriction and a decrease in GFR as reported previously. 9,11,18,19 The present investigation also confirms that chronic L-NAME treatment induces decreases in total and regional blood flow to the kidney, as well as GFR, as compared with the values obtained from nontreated control animals. As observed with chronic tempol treatment in our earlier study, 6 acute intrarenal infusion of tempol in L-NAME-hypertensive rats in the present study also increased GFR.…”
Section: Discussionsupporting
confidence: 86%
“…For example, in the normal rat, dietary sodium loading evokes a large increase in total NO production, detectable as increased U NOX V. 10,11,23,24 There is evidence that dietary sodium loading upregulates the neuronal NOS protein in the inner medullary collecting duct, 24 as well as increasing glomerular endothelial nitric oxide synthase (eNOS) messenger RNA and NO production 25 after 3 to 4 days of high salt intake. Functional studies indicate that total renal blood flow and blood flow to the papilla are under enhanced NO-dependent vasodilatory tone when salt intake is high.…”
Section: Discussionmentioning
confidence: 99%
“…9 Increased nitric oxide (NO) production occurs in response to high dietary salt intake in normal rats, and chronic NO synthase (NOS) inhibition combined with high dietary salt intake can lead to volume-dependent hypertension. [10][11][12][13] In addition, the genetically salt-sensitive hypertension in the Dahl rat is associated with defective NO production in the face of high sodium intake. 14,15 NO directly inhibits sodium transport in several parts of the tubule.…”
mentioning
confidence: 99%
“…When steps are taken to prevent increases in renal perfusion pressure, NO synthesis inhibition causes a clear fall in sodium excretion. 19 Several studies have demonstrated that the renal pressure-natriuresis mechanism is greatly impaired after administration of NO synthesis inhibitors. 20 -21 To evaluate the potential role of the renal sympathetic nerves in L-NAME-induced hypertension, we investigated the influence of renal denervation on the hypertension induced by long-term oral administration of L-NAME.…”
Section: Discussionmentioning
confidence: 99%